2010
DOI: 10.4061/2010/517060
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance inStaphylococcus aureusand Coagulase Negative Staphylococci Isolated from Goats with Subclinical Mastitis

Abstract: Antimicrobial resistance patterns and gene coding for methicillin resistance (mecA) were determined in 25 S. aureus and 75 Coagulase Negative Staphylococci (CNS) strains isolates from half-udder milk samples collected from goats with subclinical mastitis. Fourteen (56.0%) S. aureus and thirty-one (41.3%) CNS isolates were resistant to one or more antimicrobial agents. S. aureus showed the highest resistance rate against kanamycin (28.0%), oxytetracycline (16.0%), and ampicillin (12.0%). The CNS tested were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
80
5
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 20 publications
16
80
5
11
Order By: Relevance
“…Except for enroϐloxain and norϐloxacin, the present results indicate lower resistance rates to streptomycin, tetracycline and amoxicillin in Staphylococcus aureus as compared to CNS (Table 2). However, the multidrug resistant rate indicated here is higher than that (8%) recently reported in a study on antimicrobial resistance in coagulase positive and negative staphylococci from sub-clinical mastitis in goats (Virdis et al 2010).…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Except for enroϐloxain and norϐloxacin, the present results indicate lower resistance rates to streptomycin, tetracycline and amoxicillin in Staphylococcus aureus as compared to CNS (Table 2). However, the multidrug resistant rate indicated here is higher than that (8%) recently reported in a study on antimicrobial resistance in coagulase positive and negative staphylococci from sub-clinical mastitis in goats (Virdis et al 2010).…”
Section: Discussioncontrasting
confidence: 47%
“…This rate of resistance to amoxicillin was higher than that described in S. aureus from mastitis in Brazilian dairy goats (Aires-de-Sousa et al 2007) but very similar to beta-lactam resistance rates reported worldwide for Staphylococcus aureus from cattle mastitis (Rabello et al 2005, Sawant et al 2009, Virdis et al 2010.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The prevalence of subclinical mastitis in small ruminants averages 6.5 and 40.2% (6)(7)(8)(9)(10)(11)(12)(13). The (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%